Q:

A:

Logarthims of the same base can be added together by multiplying their arguments and then performing the logarithm on the product. For example, assuming log means log base 10 as it does on a calculator: log(x) + log(y) = log(x * y)

Keep Learning

Applying the definition of logarithms, we can see why this property is true. To solve log(x) = z, we do the following algebra:

10^z = x

Similarly, to solve log(y) = w, we do:

10^w = y

So, multiplying the two expressions together, we get:

(10^z)(10^w) = xy

or, 10^(z+w) = xy

Now, going in reverse, we see that this is a logarithmic expression equivalent to log(xy)

Applying the property to a problem with real numbers:

log(5) + log(3) = log(3 * 5) = log(15)

The property mentioned above is applicable to all logarithms. For example, for the natural logarithm, ln (also defined as log base e), the following is true:

ln(4) + ln(7) = ln(4*7) = ln(28).

Note that logarithms of different bases cannot be combined. For example, the following statements are both false:

ln(3) + log(9) = log(3*9)

ln(3) + log(9) = ln(3*9)

Similarly, for subtraction, the following property holds:

log(x) - log(y) = log(x/y) = log(2)

Sources:

Related Questions

• A: The integral of the secant function is the natural logarithm of the absolute value of the secant of x plus the tangent of x, plus a constant. Expressed in ... Full Answer >
Filed Under:
• A: Calculating the antilog of a number is the inverse of calculating the logarithm of a number. One is capable of determining the base "b" antilog of a number... Full Answer >
Filed Under:
• A: In calculus, the primary significance of 1/x is its value as the derivative of the natural logarithm of "x." The proof for the derivative of ln(x) may be f... Full Answer >
Filed Under:
• A: Some information on logarithms that may be included in an algebra 2 course include the relationship between logarithms and exponents and the relationship b... Full Answer >
Filed Under:
PEOPLE SEARCH FOR